Comparison of apples from organic and integrated farming - Tóth-Markus, M.; Adányi, N.; Boross, F.; Daood, H. G.; Bánáti, D.; Szabó, T.; Nyéki, J. (International Journal of Horticultural Science, 2010)
Prima’, ‘Gala’, ‘Remo’, ‘Topáz’, ‘Idared’, ‘Releika’, ‘Resi’, ‘Rubinola’, ‘Rajka’, ‘Rewena’ and ‘Florina’ apple cultivars, both from organic and integrated farming, from Pallag and Újfehértó, were compared. Average size, weight, soluble solids, titratable acidity, total polyphenols, free radical scavenging capacity expressed as Trolox equivalent (TEAC), copper and zinc were determined at harvest and after cool storage. Organic apples were more acidic, while integrated fruits had mostly higher copper and zinc content. Total polyphenols and TEAC values did not show a significant difference as a function of farming technology. A principal component analysis shows the separation of provenances as well as stored and fresh apples. Results are considered as preliminary.